(826) Selected Bibliography on Financing of Development and Related Fields ببليوجرافيا ( فهرس مراجع ) مختارة عن تمويل التنمية والمجالات المتصلة بها - Ewieda, Mohammed; Afifi, Mahmoud; Hosam El-Din, Mostafa (The Institute of National Planning, 2024)
Since its establishment, the Documentation Center of the Institute of National Planning realized the importance of bibliographical tools as an integral part of economic and social research. On the occasion of the Course on "Financing Development in African Countries" organized jointly by the Institute of Economic Development and Planning, Dakar and the Institute of National Planning, Cairo from March 4 to April 26, 1968, we introduce this Selected Bibliography Financing Development and Related Subjects in all literature received by the Documentation Center.